Simulation of rare events in communications networks. - Townsend, J.K (IEEE Communications magazine)
Computer simulation is an important tool in the analysis and design of communications networks. In spite of the advances in computational power, using simulation to obtain rare event probabilities such as cell/packet loss or delay in networks still requires prohibitively long execution times. We provide an overview of importance sampling techniques and how they can be used to provide orders of magnitude speedup for many network problems